The Effect of Capital Structure, Dividend Policy, and Firm Size on Firm Value: Evidence from PT Adhi Karya (Persero) Tbk (2014–2024) - Andi Manafe; Jeni Irnawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study examines the effect of capital structure, dividend policy, and firm size on firm value at PT Adhi Karya (Persero) Tbk during the period 2014–2024. The company’s firm value has shown fluctuations and a declining trend despite an increase in total assets, indicating a mismatch between asset growth and market perception. This study aims to analyze the influence of internal financial factors on firm value, both partially and simultaneously. A quantitative approach is employed using secondary data obtained from the company’s annual financial statements. Capital structure is measured using the Debt to Equity Ratio (DER), dividend policy using the Dividend Payout Ratio (DPR), firm size using the natural logarithm of total assets, and firm value using Tobin’s Q. Data are analyzed using multiple linear regression with the assistance of SPSS, supported by classical assumption tests, t-test, F-test, and coefficient of determination (R²). The results show that partially, capital structure and dividend policy do not have a significant effect on firm value, while firm size has a significant effect. Simultaneously, all independent variables have a significant effect on firm value. The findings indicate that firm size plays a dominant role, while other factors may also influence firm value beyond the model.